KONTRIBUSI WANITA (ISTRI NELAYAN) TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN DI KELURAHAN LERE KECAMATAN PALU BARAT - Wugaje, Fitriah M.; Hadayani, Hadayani; Baksh, Rukavina (AGROTEKBIS, 2017)
This study aims was to determine how much revenue of the fishermen and analyze the contribution of women (wives of fishermen) on fishermen income. This research was conducted in the Lere Sub District on December 2015 - February 2016. The Respondent determined by the census. Total respondents were 40 people, that all housewives who are involved in fishing activities with a fresh fish sales around the place of study. This study used analysis of income and contributes to know how big the contribution of housewives on household income of fishermen. The results showed that the revenues generated from the fisherman catches fish for 1 (one) month is Rp. 32.685.000 consisting of fresh fish sales of Rp. 17.915.000 and were processed into shredded fish and sambal roa Rp. 14.770.000. Total expenses for 1 (one) month is Rp. 21.468.329, so income obtained Rp. 11.216.671. Contributions housewife fishermen on fishermen household income is 57,15% or Rp. 6.410.327. Keyword : Fishermans wife, Fishermens Contributions wife, The wife Revenue fishermen.